World Crude Oil Markets: OPEC's Supplier Power Remains Unchallenged - Christian von Hirschhausen; Franziska Holz; Daniel Huppmann; Claudia Kemfert (Weekly Report, 2009)
In spite of the sharp decline of crude oil prices since the fall of 2008, the current price level of approximately 65 per barrel is significantly higher than the long-term average. The market power of the Organization of Petroleum Exporting Countries (OPEC), which is partially responsible for this price level, remains strong. While market prices for commodities such as coal are typically reflecting production costs, in the case of oil, market power combined with significant variations in demand leads to erratic price fluctuations. DIW Berlin's model calculations show that although OPEC cannot operate as a standard cartel, its individual members can significantly influence prices by acting as powerful oligopolists. Furthermore, over the mid-term the OPEC countries will attain even greater significance because of the size of their oil reserves.
Keywords: L13; L71; Q41; 330; Crude oil; Market structure; Cartel; Simulation model; Price indices